Odpowiedź:
z.1
- 8 = 2 x + 3
2 x = - 8 - 3 = - 11 / : 2
x = -5,5
- 6 =2 x + 3
2 x = - 9
x = - 4,5
- 5 = 2 x + 3
- 8 = 2 x / : 2
x = - 4
0 = 2 x + 3
x = -1,5
1 = 2 x + 3
-2 = 2 x
x = - 1
3 =2 x + 3
x = o
7 = 2 x + 3
2 x = 4
x = 2
Odp. Dziedzina D = { -5,5; -4,5; -4; - 1,5; - 1; 0; 2 }
Wykres tej funkcji to zbiór punktów: A = ( -5,5; 08), B = ( -4,5; -6)
C = ( - 4, -5), D = ( -1,5; 0), E = ( - 1, 1), F = ( 0, 3), G = ( 2, 7 )
z.2
f(x) = 2 *I x I - 3
a) D = { -1, 0, 1 , 3 , 4 }
f(-1) = 2*I - 1 I - 3 = 2*1 - 3 = - 1 A =( - 1, -1)
f( 0) = 2 * I 0I - 3 = 0 - 3 = - 3 B = ( 0 , - 3)
f(1) = 2*I 1 I - 3 = 2*1 - 3 = - 1 C = ( 1, - 1)
f(3) = 2* I 3 I - 3 = 2*3 - 3 = 3 E = ( 3, 3)
f(4) = 2*I 4 I - 3 = 2*4 - 3 = 5 F = ( 4, 5)
Wykresem tej funkcji jest zbiór punktów : A, B, C, D, F
b) Robimy analogicznie.
Szczegółowe wyjaśnienie: